Membrane asymmetry imposes directionality on lipid droplet emergence from the ER - Chorlay, Aymeric; Monticelli, Luca; Veríssimo Ferreira, Joana; Ben M’barek, Kalthoum; Ajjaji, Dalila; Wang, Sihui; Johnson, Errin; Beck, Rainer; Omrane, Mohyeddine; Beller, Mathias; Carvalho, Pedro; Rachid Thiam, Abdou (Developmental cell, 2019)
Summary: During energy bursts, neutral lipids fabricated within the ER bilayer demix to form lipid droplets (LDs). LDs bud off mainly in the cytosol where they regulate metabolism and multiple biological processes. They indeed become accessible to most enzymes and can interact with other organelles. How such directional emergence is achieved remains elusive. Here, we found that this directionality is controlled by an asymmetry in monolayer surface coverage. Model LDs emerge on the membrane leaflet of higher coverage, which is improved by the insertion of proteins and phospholipids. In cells, continuous LD emergence on the cytosol would require a constant refill of phospholipids to the ER cytosolic leaflet. Consistent with this model, cells deficient in phospholipids present an increased number of LDs exposed to the ER lumen and compensate by remodeling ER shape. Our results reveal an active cooperation between phospholipids and proteins to extract LDs from ER.
Gesehen am 20.08.2019